Prevalence trends of hypertension and influence factors among children and adolescents aged 7–17 years in China, 2011–2015: A serial cross-sectional study - Yang, Yunjuan; Dai, Jing; Min, Jieqing; Wu, Huamei; Huang, Songquan; Li, Qingsheng; Chai, Jiajia (Frontiers in Public Health, 2022)
Hypertension has rapidly increased in the last decades throughout the world. It is an emerging disease. However, limited information is available on secular trends and factors of childhood and adolescents' hypertension in China. In this study, 5-year successive data were derived from a cross-sectional study of the China Health and Nutrition Survey (CHNS) in 2011 and 2015. We used systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) at least 95th percentile on the basis of age, sex, and height percentiles to define hypertension (HBP). A total of 2,827 children and adolescents aged 7–17 years were included. The age-standardized prevalence of hypertension was increased significantly across 5 years: the standardized prevalence of hypertension was increased from 8.08% (2011) to 11.46% (2015) in China (P < 0.01). The mean SBP of boys increased from 101.21 to 102.79 mmHg, while the mean SBP of girls increased from 98.96 to 100.04 mmHg. The mean DBP of boys increased from 61.20 to 67.40 mmHg, while the mean DBP of girls increased from 64.34 to 65.76 mmHg. The prevalence of hypertension grew continuously in both sexes, but the pace of change for boys was more rapid than that for girls. This study confirmed that the association between rural (odds ratio [OR] = 1.394, 95%CI 1.032–1.883), overweight/obesity (OR = 2.621, 95%CI 1.506–4.562), and BP levels was highly correlated (P < 0.05). The possible protecting factors associated with hypertension were being a girl (OR = 0.788, 95%CI 0.595–1.043). There was no association between weekly physical activity, daily sleep duration, and hypertension (P > 0.05). Further in-depth analysis of influencing factors and comprehensive interventions should be urgently implemented to combat the hypertension epidemic among children and adolescents in China.